Evaluation of Some Properties of Distributed Databases using Oracle - Alaa Saeed Al-Mukhtar (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this study, query processing efficiency of the distributed database in the relational database Oracle9i was examined and compared. Our test data is based on a (Customer Type Definition), which is designed to represent customer information of bank. We generated 8 different sizes of test customers: 300, 600, 900, 2100,4500, 45000, 1360 Records. DML language (SQL) as tools for any comparison can be achieved by the statistical performance parameter (Elapsed time, CPU time, Logical read , Physical read, Logical write, Physical write, Elapsed time, UGA ) .statistical analysis using ANOVA TABLE is used to judge between comparisons. All the queries were run on two computers for different sizes of vertical and horizontal fragments. Changes in performance metrics for each query were written in table after experiments. Finally, we presented the results, and discussed where enhancements are required. Statistical analysis using ANOVA TABLE were used to distinguish  between this comparison,  it had been  found that SELECT, UPDATE and DELETE have the most influence on the performance parameter respectively.